Standard Test Method for Rockwell Hardness of Plastics and Electrical Insulating Materials - Astm
This test method covers two procedures for testing the indention hardness of plastics and related plastic electrical insulating materials by means of the Rockwell hardness tester.
Keywords: PLASTICS AND ELECTRICAL INSULATING MATERIALS